Objectification of the superconcept «ideology» in the publicistic discours: diachronic aspect - Baimamyrov, S.A.; Tungushbaeva, B.K. (KSU Publ., 2020)
The authors considers the phraseological — periphrastic combination in the conceptospher of the superсonсept «ideology» that exist in the minds of members of social groups in the form of linguistic representations, define group identity and are included in the body of political lexicon, as one of the highlights of the Russian language will the Soviet / post-Soviet period. Our research is devoted to an actual problem of the modern linguistic science — cognitive theory, particularly to structure and semantic study of the superconcept «ideology». In the article described over phrase combinations OPHC of the Russian language, verbalizing this concept in publicistic discourse of the Soviet and beginning of the Post Soviet periods. Theoretical importance of the offered research is defined by the development of the Russian language conceptosphere theory, author’s attempt to work out OPhC theory, ordering principles, underlining and describing them in pragma linguistic aspectpractical. The authors of the article also present various schemes and tables, illustrating the theoretical provisions of the work.
«Идеология» суперконцепциясының публицистикалық дискурста белгіленуі: диахрондық аспект
Объективация суперконцепта «идеология» в публицистическом дискурсе: диахронический аспект
Keywords: language; ideology; linguistic representations; political lexicon; conceptosphere; social groups; publicism